Role of inert gas to reduce mechanical defects of the built object fabricated by SLM process / Mohamed I Hamed Elgadari - Mohamed I, Hamed Elgadari (2018)
The use of additive manufacturing (AM) technology has been expanding dramatically last few decades, especially in the industrial sector. The need of switching from the mass production to individual production has led to increase the interest to the additive manufacturing especially selective laser melting (SLM). The quality of a SLM object depends on few parameters such as laser power, scanning speed, and inert gas. In this project, the effect of inert gas on the microstructure and mechanical properties of an austenitic stainless steel was investigated. For this reason, two samples were studied. At the beginning of the manufacturing process, the Argon gas was present. However, near to the end of the process, the Argon gas had run out and the process continued without an inert gas. The laser power used for both samples was 360 W while scanning speeds were 250 and 510 mm/s respectively. The tensile strength as well as micro hardness was studied to investigate the mechanical properties. Microstructure observation was performed using optical microscope and (SEM). Microstructure for both samples was performed in 3 sections which represent the lower, middle and upper part of the sample. Results show that, high porosity was observed in section 3 while in the other sections the porosity status was lower than section 3. Microhardness test showed that, the average hardness at section 3 for sample 1 and 2 was 192 and 205 HV which is higher than other sections. Tensile test results show that the ultimate tensile strength and yield strength for sample 1 were 482 MPa and 245 MPa respectively. However tensile results for sample 2 showed an enhancement on these properties. After the samples were broken, it was noted that the fraction occurred at a section near to the top of the sample which was formed after finishing the inert gas. The reason for that might be due to the high porosity at that section that caused stress concentration.